A developmental and constructionist perspective on social entrepreneur mobilisation. (1st January 2014) - Kury, Kenneth Wm.
This paper delves into an individual's mobilisation to social action and puts forth theoretically grounded propositions to predict who is likely to mobilise as well as moderators of the mobilisation to social action. Concentrating on the mobilisation of action rather than on 'successful' social entrepreneurs, typical of case studies, accomplishes two things. It moves the social entrepreneur literature dialog away from a 'great person' discussion to a dialog surrounding established theoretical frames, and broadens the study of social entrepreneurs to include those who potentially could seek to make social change. This is accomplished by exploring the role of developmental psychology and social construction in contributing to the potential change agent's mobilisation via a dialectic process. The paper presents a dialect model of social entrepreneur mobilisation along with a set of propositions and discusses methodological issues and implications of incorporating a dialect frame into the emerging social entrepreneur research stream.